The ethical soundscape : cassette sermons and Islamic counterpublics. - Hirschkind, Charles (Cultures of history., 2006)
An essential aspect of what is now called the Islamic Revival, the cassette sermon has become omnipresent in most Middle Eastern cities, punctuating the daily routines of many men and women. Hirschkind shows how sermon tapes have provided one of the means by which Islamic ethical traditions have been recalibrated to a modern political and technological order—to its noise and forms of pleasure and boredom, but also to its political incitements and call for citizen participation. Contrary to the belief that Islamic cassette sermons are a tool of militant indoctrination, Hirschkind argues that sermon tapes serve as an instrument of ethical self-improvement and as a vehicle for honing the sensibilities and affects of pious living -- Présentation de l'éditeur.